DEVELOPMENT OF SOCIAL NETWORKS IN EMPOWERING OF RELIABLE DAILY WORKERS IN CIKIDANG VILLAGE DISTRICT LEMBANG BANDUNG BARAT REGENCY - Samudraman Harefa; Lina Favourita; Aribowo Aribowo (Politeknik Kesejahteraan Sosial Bandung, 2018)
The purpose of this study is to obtain an overview of the condition of Daily Workers in managing doll-making and social networking businesses that include networks, emotional networks, and government support networks in managing puppet-making businesses. The research method used is action research method. Data sources are primary and secondary data sources. The primary data source is Daily Worker in Cikidang Village. Data collection techniques were conducted with in-depth interviews, participatory observation, and documentation studies. Data validity test used is credibility test, transferability test, dependability test and confirmability test. Analytical techniques used are qualitative data analysis techniques. The results show that through the social networking development desain for Daily Workers can develop networks, emotional networks, and government support networks and increase the productivity of Daily Workers in Cikidang Village in managing doll making business.